Perfluoroalkyl substances (PFASs) and other halogenated compounds in fish from the upper Labe River basin. (June 2015) - Svihlikova, Veronika; Lankova, Darina; Poustka, Jan; Tomaniova, Monika; Hajslova, Jana; Pulkrabova, Jana
Highlights: 25 PFASs and 11 BFRs were on the list of target analytes. The first monitoring of OH-PBDEs and brominated phenols in the Czech environment. PFOS, C9–C14 PFCAs, FOSA and α-HBCD were most prevalent compounds. PFAS and BFR levels were lower than those in industrialized areas worldwide. Abstract: This study summarizes results on levels of 25 perfluoroalkyl substances (PFASs), three hexabromocyclododecane isomers (HBCDs), tetrabromobisphenol A (TBBPA), three brominated phenols and four hydroxylated derivates of polybrominated diphenyl ethers (OH-PBDEs) in 59 fish samples collected in nine localities on two major rivers from the Czech Republic. To identify potential sources of these chemicals, several sampling sites located close to highly industrialized areas were also involved. The major PFAS representatives, perfluorooctane sulfonate (PFOS), C9–C14 perfluoroalkyl carboxylic acids (PFCAs) and perfluorooctane sulfonamide (FOSA) were detected in 100% fish samples. The concentration ranges of individual substances in the respective groups of PFASs were as follows: 0.572–61.3 ng g − 1 wet weight (ww) for Tot-PFOS, 0.007–0.121 ng g − 1 ww for perfluoroalkane sulfonates (PFSAs) (without PFOS isomers), 0.007–22.0 ng g − 1 ww for PFCAs and 0.026–7.76 ng g − 1 ww for FOSA. The highest contents of ∑PFASs (51.9 ng g − 1 ww and 47.8 ng g − 1 ww) were measured in fish muscle tissue from the locality Trmice situated on the Bílina River and Verdek on the Labe River, where chemical and/or textile industry is located. From 11 targeted BFRs, five compounds (α-HBCD, β-HBCD, γ-HBCD, TBBPA and 2, 4, 6-tribromophenol (TBP)) were determined in analyzed samples. The concentration ranged as follows: 3.15–1211 ng g − 1 lipid weight (lw) for ∑HBCD, 4.99–203 ng g − 1 lw for TBBPA and 1.76–107 ng g − 1 lw for 2, 4, 6-TBP.